Synthesis and Structure of Fe(III) Complex Derived from An Octadentate Schiff Base Ligand - Jiang, Guang-Qi; Lu, Yong-Zhong (Asian Journal of Chemistry, 2013)
A new Fe(III) complex, [Fe(C26H26O3N4)]NO3.H2O, was obtained by the reaction of Schiff base ligand H4L H4L = 1,1,1,1-tetrakis[(salicylaldimino)methyl]methane with Fe(NO3)3.9H2O at 1:2 mol ratio and was structurally determined by elemental analyses, IR, EI-MS and single crystal X-ray diffraction analysis. The complex crystallized in the monoclinic system, space group P 21/n with unit cell parameters: a = 12.486(5) Å, b = 15.769(5) Å, c = 12.989(5) Å, b = 95.764(5)°, V = 2544.5(16) Å3, Z = 4, Mr = 578.38, Dc = 1.510 g/cm3, μ = 0.650 mm-1, F(000) = 1204, R = 0.0400, wR = 0.1109 for 3701 reflections with I >2s (I). It is of interest to note that one of the pendant arms of H4L ligand was hydrolyzed when H4L coordinated with Fe(III) ions, simultaneously, the resulting amino group was protonated to maintain the charge balance of the system.